Skill of donning surgical gloves amongst residents: a neglected skill - Kasula, Jayasree; Yerroju, Kodandapani (International Surgery Journal, 2019)
Background: Sepsis is a preventable cause of morbidity and mortality. Sepsis causes approximately 1 million new-born deaths annually. The global prevalence of maternal sepsis is 4.4% causing more than 5.7 million cases and one tenth of maternal deaths annually. Skin preparation, shaving and wound closure were some factors involved in surgical site infections. But the technique of wearing gloves in a sterile way has not received enough attention. Hence this cross sectional observational study was undertaken to assess the awareness and proficiency in this technique among the residents. Methods: 104 post graduate students from the departments of General Surgery, Obstetrics and Gynaecology, Paediatrics and Anaesthesiology from two medical colleges were administered a questionnaire and also were observed one at a time with a checklist in an OSCE station. Study was conducted in several sessions over a period of 2 months. Results: None of them were formally taught this technique. 36 (34.56%) were informally taught by seniors. 7 (6.72%) tore the glove while wearing. 39 (37.44%) put two fingers in one finger space. 42 (40.32%) touched bare skin with gloved hands while wearing. 54 (51.84%) touched bare skin with used surface of the glove while removing. Conclusions: Awareness about technique and skill of donning sterile gloves among residents of various specialities are not satisfactory. It is recommended to teach this skill as soon as the students enter medical school in a strict and formal way and monitor their proficiency throughout their training period.